Modelling of Permeation Grouting considering Grout Self-Gravity Effect: Theoretical and Experimental Study. (27th November 2019) - Fu, Yanbin; Wang, Xiuling; Zhang, Sizhan; Yang, Yong
Abstract : Self-gravity is one key parameter for behavior characterization of grout permeation and diffusion. This study proposes mathematical models for permeation grouting with consideration of grout self-gravity effect. The models concerning power law, Bingham, and Newtonian grouts are based on the generalized Darcy's law and spherical diffusion theory. In addition, a prediction model of grout concretion dimension used for Bingham grout was developed. An analysis of the injection pressure distribution law and a comparative evaluation of diffusion radius considering self-gravity effect using established models were conducted subsequently. Moreover, grouting experiments were performed to check and verify the prediction model. The experimental results showed that injection pressure decreases linearly with increase of diffusion radius for the power-law grout, while nonlinear decrease of injection pressure was confirmed in Bingham and Newtonian grouts in this case. Three grouts approximately diffuse in an "ellipsoidal" shape, and it is confirmed that the diffusion radius is closely related to grout self-gravity. The Newtonian grout produces the maximum diffusion radius compared with the other two grouts whether the gravity effects were considered or not. The grout quantity under a smaller water-to-cement w / c ratio exhibits a significant difference and undergoes two increasing stages, whereas the quantity simply tends to be stable after it reaches its maximum in terms of the larger w / c ratios. The constructed dimension prediction model agrees well with the experimental results, which can be helpful for design and assessment of the grouting scheme.